Comparative solutions to improve English in public education systems of triglossia Philippines, India, South Africa and Singapore - Uychoco, Marikit Tara Alto (2008)
This study aimed to find out what has been done in the Philippines and other multilingual countries with Triglossia such as India, South Africa, and Singapore, to strengthen their own English Language competencies. After profiling each country's programs and policies, a cost-benefit analysis of solutions to English language teaching problems was made. The current Philippine public education system's policies and practices were then compared in the hope of helping Philippine teachers and administrators have alternative solutions to improve their English language skills. Through the comparative study, it was concluded that several initiatives and programs still need considerable improvement. There is a need for each school to be aware of the innovations and measures done by other schools in order to improve their own performance and to think of ways to incorporate good practices in their schools.